Adoption Status and Perception of Farmers on Improved Tef Technology Packages: Evidence from East Gojjam Zone, Ethiopia - Atrsaw Anteneh Mihretie; Girmachew Siraw Misganaw; Negussie Siyum Muluneh (Advances in Agriculture)
Tef is a major staple crop in Ethiopia and Eritrea. Many improved Tef varieties were released from the Ethiopian research institute in the past three decades. Information on the farmers’ adoption status and perception on released improved Tef technology have paramount importance for launching new and modifying Tef technology packages. However, such information is meager in Ethiopia. Therefore, this study was conducted to assess farmers’ status and perception of improved Tef technologies. A multistage random sampling technique was employed to select sample of 224 Tef grower farmers. The results were interpreted and discussed using descriptive and inferential statistics. The result indicated that farmers in the study area found at the medium level of adoption of Tef production technology (i.e., the average adoption index is 0.43). The findings also confirm that farmers perception towards the relative advantages of improved Tef varieties shows that high grain yield, good germination, early mature, and disease resistance capacity were perceived as the most crucial attributes of improved Tef varieties, whereas straw quality and tolerance to lodging were perceived as the least important attributes of the technology. Therefore, efforts and commitments to be expected from plant breeders and genetic specialists to reduce lodging of Tef through hybridizing semidwarf Tef varieties.